Estimating strategic responses to the march of a low cost carrier to primary airports. (January 2018) - Bettini, Humberto F.A.J.; Silveira, José Maria F.J.; Oliveira, Alessandro V.M.
Highlights: We study the capacity formation of incumbent airlines of a multiple airports region. We analyze a "march" of an LCC from a secondary to the existing primary airports. We inspect the impacts of different degrees of LCC entry threat. Preemption may have raised relevant entry barriers at the studied primary airports. Abstract: We empirically investigate the capacity responses of major incumbent airlines facing the entry of a new low cost carrier in a secondary airport of a multiple airports region. We develop an empirical model that allows for time-varying strategic responses, aiming at identifying possible degrees of route entry threat. We consider the case of the entry of Azul Airlines in the densest conurbation in Brazil. Our results suggest that the incumbents preemptively fortified their flight frequency positions on threatened routes to deter the anticipated march of the newcomer from the secondary airport toward the existing primary airports.